IMPLEMENTASI KEBIJAKAN PENERTIBAN LALU LINTAS TRUK BERTONASE BESAR DI KOTA PEKANBARU - Lisa Olivia Saputri; Hasim As'ari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The law No. 22 of 2009 concerning Road Traffic and Transportation, it has a strategic role in supporting development and national integration as part of efforts to promote public welfare and to realize road traffic and transportation in Pekanbaru City so that it is safe, smooth, orderly and efficient. However, the implementation of Law No. 22 of 2009 still reaps various kinds of problems, namely the discipline of road users in traffic is still not achieved, especially in the city of Pekanbaru itself. This study aims to see how it is implemented in traffic and to find out what are the inhibiting factors in the implementation of traffic and road transportation policies in Pekanbaru City. The method used in this research is descriptive qualitative method using Yulianto Kadji's theory which consists of several indicators such as mentality, system, and networking. The results of this study indicate that the implementation of traffic and road transportation policies in Pekanbaru City has been carried out well by the apparatus, but the participation of truck drivers' awareness is still not good so they still commit violations even though the policy has been issued. Supervision cannot be carried out continuously due to the lack of human resources. The researcher also advises that the legal apparatus should be more active in conducting raids in places that often commit violations based on information provided by the local community in order to create smoothness and comfort and safety for road users. Keywords: Policy Implementation, Traffic, Road Transportation